Inonotus rickii (Agaricomycetes, Hymenochaetaceae) in Brazilian Cerrado: Expanding Its Geographic Distribution and Host List - Leonardo-Silva, Lucas; Abdel-Azeem, Ahmed M.; Xavier-Santos, Solange (Frontiers in Microbiology, 2021)
Inonotus rickii (Pat.) Reid (Agaricomycetes: Hymenochaetaceae) is a poroid fungus characterized by the expressive production of chlamydospores, in vivo and in vitro, especially during its anamorphic stage. The species plays important ecological roles, standing out as a phytopathogen, affecting several species of ornamental and wild trees, mainly in tropical and subtropical regions. The infected trees develop canker and white rot of the wood, showing symptoms of reduced vegetative vigor and decline of leaves and branches which causes death in some cases. The first record of I. rickii for the Cerrado biome (Brazilian Savanna) and the first record as causal agent of canker in Schinus molle L. in Brazil is reported here. In addition, we present a checklist of its worldwide geographical distribution and known hosts, from an extensive bibliographic search in Google Scholar, SciELO, Scopus, and Web of Science databases. The species is widespread in tropical and subtropical zones; common in the American continent, especially in Central and South America and the Mediterranean region, and rare in temperate zones. We found specimens growing in both living and dead hosts, totalizing 70 species of hosts, distributed in 43 genera and 22 families. Of these, Acer negundo L. (10.5%), Celtis australis L. (6.5%), and Platanus acerifolia (Aiton) Willd. (4.8%), and the Fabaceae (30%), Fagaceae (10%), and Sapindaceae (8.6%) families were the most frequent. We present morphological descriptions and illustrations, as well as the growth characteristics in culture medium. Our study expands the known geographical distribution of I. rickii, including the Cerrado biome, as well as its structural, physiological characteristics, and its hosts.